Patient-Tailored Aortic Valve Replacement - De Backer, Ole; Wong, Ivan; Wilkins, Ben; Carranza, Christian Lildal; Søndergaard, Lars (Frontiers in Cardiovascular Medicine, 2021)
Contemporary surgical and transcatheter aortic valve interventions offer effective therapy for a broad range of patients with severe symptomatic aortic valve disease. Both approaches have seen significant advances in recent years. Guidelines have previously emphasized ‘surgical risk’ in the decision between surgical aortic valve replacement (SAVR) and transcatheter aortic valve replacement (TAVR), although this delineation becomes increasingly obsolete with more evidence on the effectiveness of TAVR in low surgical risk candidates. More importantly, decisions in tailoring aortic valve interventions should be patient-centered, accounting not only for operative risk, but also anatomy, lifetime management and specific co-morbidities. Aspects to be considered in a patient-tailored aortic valve intervention are discussed in this article.